The Use Of Nutrition Labels As Mediation Of The Influence Of Nutrition Knowledge, Motivation And Consumer Attitudes On Consumer Purchasing Decisions In Indonesia - Rifani, Ahmad; Maya Sari Dewi; Muhammad Zainal Abidin; Gusti Rina Fariany; Indiani Risty Agustia; Syamsa Siroja (Cita Konsultindo Research Center, 2025)
This study aims to find out and analyze: (1) the effect of nutritional knowledge on the use of nutrition labels on Le Minerale products, (2) the influence of motivation on the use of nutrition labels on Le Minerale products, (3) the influence of attitudes on the use of nutrition labels on Le Minerale products (4) the effect of the use of nutrition labels on Le Minerale products on purchase decisions. This type of research is in the form of quantitative research. The population used in this study is generation Z in Indonesia aged 17 to 28 years and has bought Le Minerale products. Data was collected from 122 respondents. The sampling technique used in this study is purposive sampling using a questionnaire. The data analysis technique used is SEM PLS. The results showed that (1) nutrition knowledge had a positive and significant effect on the use of nutrition labels on Le Minerale products, (2) motivation had a positive and significant effect on the use of nutrition labels on Le Minerale products, (3) attitudes had a positive and significant effect on the use of nutrition labels on Le Minerale products, (4) the use of nutrition labels on Le Minerale products had a positive and significant effect on purchase decisions, (6) the use of nutrition labels as a moderation of the influence of motivation on purchasing decisions had a significant effect, while nutrition labels as a moderation of the influence of attitudes on purchasing decisions did not have a significant effect.